2013
DOI: 10.1016/j.yebeh.2013.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Association between knowledge and attitudes of educators towards epilepsy and the risk of accidents in Greek schools

Abstract: Accidents in children with epilepsy are an actual concern of teachers and parents in Greece and internationally. The aim of this study was to investigate the relationship between the knowledge and attitudes of teachers and the frequency of accidents caused by epilepsy in Greece. The study surveyed 1404 public elementary school teachers from all prefectures of the country by an anonymous questionnaire. Results showed that teachers cannot always recognize the manifestations of an epileptic seizure or an injury c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Kampra et al 25 reported that with respect to hindering school attendance Greek teachers felt that heart disease was most the important followed by epilepsy, diabetes and asthma. Toli et al 38 reported that Greek teachers perceived epilepsy as the most difficult condition to manage in school compared to cancer, diabetes and asthma. Bishop and Boag (2006) 13 considered teacher familiarity with seven conditions.…”
Section: Studies Which Included Comparison Conditionsmentioning
confidence: 99%
“…Kampra et al 25 reported that with respect to hindering school attendance Greek teachers felt that heart disease was most the important followed by epilepsy, diabetes and asthma. Toli et al 38 reported that Greek teachers perceived epilepsy as the most difficult condition to manage in school compared to cancer, diabetes and asthma. Bishop and Boag (2006) 13 considered teacher familiarity with seven conditions.…”
Section: Studies Which Included Comparison Conditionsmentioning
confidence: 99%
“…School teachers with correct knowledge of and appropriate attitudes toward epilepsy could put the social reflections of epilepsy in a correct perspective, thus contributing to the reduction of stigma. Public knowledge and attitudes toward epilepsy have been investigated in several countries and have been found to be mostly inadequate [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Time spent in teaching and experience with students with epilepsy predict better knowledge of the disease [7,10,16].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed it appears to have been a typical duty of each resident to have some information about the expertise of delivering First Aid, so various occurrences can be forestalled. Emergency treatment is the valuable wellspring of the essential consideration gave to a harmed individual or the person who abruptly becomes sick (Toli et al, 2013). Treatment of First Aid as a term is on-spot care given to an individual, who is genuinely harmed or mentally bothered with morals of any difficulty (Fritz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%